A contribuição da educação física escolar para a autonomia da prática de atividade física de alunos finalistas do ensino médio - Oliveira, Raquel Procópio de (Brasil, 2023)
The objective of this study was to highlight the contribution of school physical education to the autonomy of the practice of physical activity and of the egress. More specifically, we sought to: address the concept of physical activity, its importance and its benefits in the lives of those who practice it; to infer about the importance of school physical education for the autonomy of graduates and to report the experience of conducting the internship during physical education classes with third-year high school classes, the future graduates. Data were collected from the application of two questionnaires, an initial one containing 5 questions and a final one, after practical classes during the conducting, containing 4 questions. Students from two classes of the 3rd year of high school at a public school located in the city of Manaus participated. In all, there were 85 students of both genders, 48 students belonging to the 3rd year 1 and 37 students belonging to the 3rd year 3. The results indicated that the greater contribution of School Physical Education to acquiring autonomy, in addition to the theoretical knowledge they have about the subject is in encouraging the practice of physical activity, with the activities carried out and with the teacher's planning and strategies through the application of their lesson plans.